Cooperation after exit: how informality is sustaining EU–UK cooperation on sanction negotiations. - Lovato, Marianna (International Affairs, 2026)
How do voluntary withdrawals from an international organization (IO) affect future cooperation between the exiting state and the remaining members? And how do these withdrawals affect the capabilities of the IO itself? The answers to these questions are key to understanding how European security architecture evolved after Brexit and how the United Kingdom's role in Europe's security governance consequently changed. Relying on interviews with diplomats and European Union officials as well as document analysis, this article traces the evolution of the UK's role in pre- and post-Brexit sanctions negotiations (in 2014 and 2022, respectively). Against all expectations, Brexit did not fundamentally obstruct UK–EU27 cooperation on Ukraine. The article contends that converging security interests and existing informal channels allowed for post-withdrawal cooperation to continue. Within these informal extra-EU coordination venues, the UK continued to work closely with the EU27 on sanctions policy, playing an important role in the response to the war more generally. However, without the formal powers afforded by EU membership, the UK's ability directly to shape the EU's foreign and security policy has diminished significantly. The EU's own sanctions capabilities, on the other hand, have not been significantly hampered by Brexit. The article contributes to the International Relations literature on voluntary withdrawals by showing how informality can help sustain cooperation between the exiting country and remaining member states.